2004
DOI: 10.1172/jci200421086
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial hypoxia-inducible factor-1 is protective in murine experimental colitis

Abstract: Mucosal epithelial cells are uniquely equipped to maintain barrier function even under adverse conditions. Previous studies have implicated hypoxia in mucosal tissue damage resulting from both acute and chronic inflammation. Given the importance of the transcriptional regulator hypoxia-inducible factor-1 (HIF-1) for adaptive hypoxia responses, we hypothesized that HIF-1 may serve as a barrier-protective element during mucosal inflammation. Initial studies of hapten-based murine colitis revealed extensive mucos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

30
475
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 518 publications
(516 citation statements)
references
References 49 publications
30
475
4
Order By: Relevance
“…Moreover, Vascular endothelial growth factor-dependent angiogenesis appears to be an integral part of human IBD [14]. In support of these hypotheses, studies in murine models have identified the epithelium as the central target of hypoxia during active mucosal inflammation [15]. As part of our ongoing work, we have confirmed the existence of mucosal hypoxia in murine models of IBD using 2-nitroimidazole dyes, a class of compounds known to undergo intracellular metabolism depending on the availability of oxygen within tissue (Fig.…”
Section: Hypoxia and Mucosal Inflammationmentioning
confidence: 90%
See 3 more Smart Citations
“…Moreover, Vascular endothelial growth factor-dependent angiogenesis appears to be an integral part of human IBD [14]. In support of these hypotheses, studies in murine models have identified the epithelium as the central target of hypoxia during active mucosal inflammation [15]. As part of our ongoing work, we have confirmed the existence of mucosal hypoxia in murine models of IBD using 2-nitroimidazole dyes, a class of compounds known to undergo intracellular metabolism depending on the availability of oxygen within tissue (Fig.…”
Section: Hypoxia and Mucosal Inflammationmentioning
confidence: 90%
“…Accumulation of nitroimidazole adducts, particularly in the epithelium, were as intense as those observed in some tumors, suggesting the existence of intense foci of hypoxia associated with these inflammatory lesions. While we do not yet know the basis for such inflammatory hypoxia, some evidence suggests that tissue vasculitis could predispose epithelia toward diminished oxygen delivery [15].…”
Section: Hypoxia and Mucosal Inflammationmentioning
confidence: 99%
See 2 more Smart Citations
“…Peripheral tissues, even under homeostatic conditions, are characterized by site-specific low oxygen tension, and O 2 availability is further limited in the context of injury/inflammation, with increased O 2 consumption by infiltrating immune cells, and swelling/edema heightening the distance to the nearest blood vessel (3)(4)(5)(6)(7).…”
mentioning
confidence: 99%